INTERACTIVE EFFECT OF AIR POLLUTION AND NUTRIENTS ON BIOCHEMICAL PROCESSES AND YIELD OF WHEAT GROWN IN PERI-URBAN AREAS OF ALLAHABAD CITY - Agrawal, S. B.; Singh, Anoop; Rathore, Dheeraj (Ecoprint: An International Journal of Ecology, 2004)
Agricultural production is greatly affected by the increase of urban air pollution in many cities of India and other developing countries. The present field study investigated the interacting effect of air pollutants and mineral nutrients on physiological and biochemical processes and yield of wheat (Triticum aestivum L. var. HD 2329) plants grown in pots from germination to maturity having similar edaphic conditions at nine sites in periurban areas of Allahabad city having different concentration of air pollutants. SO2, NO2 and O3 in ambient air were found in the ranges between 2.5 to 42.5, 10.13 to 65.04 and 3.33 to 30.83 μg m-3, respectively. Various physiological and biochemical processes showed adverse effect at sites receiving higher pollution load. Reduction in photosynthetic pigments, protein and ascorbic acid contents was noticed with an increase in pollution load, while phenol content was increased. Higher reduction in grain yield was noticed at heavily polluted sites. Fertilizer amendment showed positive response in minimizing the negative impact of air pollution by increasing the photosynthetic pigments and yield of wheat plants. The present investigation also suggests that urban air quality of Allahabad city is affecting the agricultural production unfavorably in periurban areas. Key words: Air pollution, mineral nutrients, photosynthetic pigments, protein, yield, Triticum Ecoprint Vol.11(1) 2004